Selection of molding sands for thin-walled cast iron castings, including testing of their selected properties - Major-Gabryś, Katarzyna; Drożyński, Dariusz (My University, 2025)
This report shows the results achieved within NetCastPL4.0 project. The project is being realized in cooperation between AGH Faculty of Foundry Engineering (Leader), CNR-ICMATE and Aalto University School of Engineering. This report is a part of research focused on elaboration of molding materials used for advanced light-weighting castings production and their use in light-weight cast iron castings. Elaboration of molding materials used for advanced light-weighting castings production is also the milestone of the project. As part of the development of molding compounds for thin-walled castings, compounds with organic binders and compounds with inorganic binders were tested. Tests were carried out on the tensile and bending strength, permeability, and friability of the compounds. For selected mixes, tests were carried out on their thermophysical properties (hot distortion parameter), gas generation, and thermal degradation.